(untitled) (Studia Prawnicze / The Legal Studies, 1982)
This study deals with the problem of acquisition of right to additional payment for work performed in dangerous, ardous or unhealthy conditions (such payment being an element of remuneration for work). Significance of this benefit payable by work establishment is connected with the fact that is contitutes an instrument of protection of widely understood interests of employees peforming work in particularity ardous conditions, or these threatening their health or life. For this problem, normative notion of ardous, unhealthy or dangerous con- ditions was significant, since performance of work in such conditions generally constitutes a requirement for the acquisition of right to an addition. Normative notion of ardous, unhealthy and dangerous conditions of work is narrower than the corresponding one applied in natural science, and it is not identical to com- mon understanding of these terms. Considering applied normative solutions, the issue of acquisition of right was presented separately for additional payment for work in ardous and unhealthy conditions, and additional payment for work in dangerous conditions, without violating, however, the homogeneity resulting from the fact that in both cases we are dealing with benefits connected with performance of work in threatening conditions. Grammatical interpretation of norms stating the right to additional payment for work in ardous or unhealthy conditions indicates separation of two issues:acquisition of right, and its realization. According to binding norms acquisition of right is conditioned by the fact of performing work in threatening conditions, and its realization by working in such conditions for a defined period of time. Con- sidering particular need to protect interests of employees performing their work in ardous, or unhealthy conditions, in this study we present the view, that binding normative solution considers required period of work as condition to pay addition- al payment, and not to acquire the right to it. Also systematic interpretation argues in favour of such reasoning, because the whole issue constitutes an in- divisible unity; and in case of dangerous conditions acquisition and realization of right to additional payment are not conditioned by any requirement as to the period of work performed in dangerous surroundings. Hence, in this study, we presented our opinion according to which begining with the moment of resuming work in ardous, unhealthy or dangerous conditions an employee acquires an expectation to additional payment (temporary -subjective right), which is later transformed into “common” right, when condition precedent foreseen in the norm is fulfilled (i.e. an employee works in such conditions during a defined period of time). It seems that presented solution has this favourable feature that it allows an employee to acquire strong legal position already in the moment the work in threatening conditions has begun, since he benefits from protection of the acquired temporary right.